Electrolytic capacitor and method for manufacturing same
By forming a porous portion, a dielectric layer and a solid electrolyte layer on the surface of the anode body of the electrolytic capacitor, and forming a multi-layer conductive polymer layer by coating and drying multiple treatment liquids, the shortcomings of the electrolytic capacitor in terms of high voltage withstandness and leakage current suppression are solved, and efficient capacitance performance is achieved.
Patent Information
- Application Number
- CN202411307673.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-09-19
- Publication Date
- 2025-03-28
AI Technical Summary
The existing electrolytic capacitors have shortcomings in high voltage withstandability and leakage current suppression, especially in the thickness of the solid electrolyte layer and the heat shrinkage and stress problems arising during the formation process.
By forming a porous portion, a dielectric layer and a solid electrolyte layer covering the dielectric layer on the surface of the anode body of the electrolytic capacitor, the specific process includes preparing the anode body, forming a dielectric layer and a solid electrolyte layer, processing with a treatment liquid containing a conductive polymer and repeating the drying or polymerization process to form a multi-layer conductive polymer layer.
The high voltage withstandability and low leakage current of the electrolytic capacitor are achieved. By controlling the thickness and number of layers of the solid electrolyte layer, the stress caused by heat shrinkage is reduced, the defects of the dielectric layer are reduced, and the lowness of equivalent series resistance (ESR) is improved.
Smart Images

Figure BDA0005049739250000281 
Figure HDA0005049739260000011
Abstract
Description
Technical Field
[0001] The present disclosure relates to electrolytic capacitors and methods of manufacturing the same. Background Art
[0002] An electrolytic capacitor comprises a capacitor element, an outer casing that seals the capacitor element, and an external electrode electrically connected to the capacitor element. The capacitor element comprises: an anode body having an anode lead-out portion including a first end portion and a cathode forming portion including a second end portion; a dielectric layer formed on a surface of at least the cathode forming portion of the anode body; and a cathode portion that covers at least a portion of the dielectric layer. The cathode portion comprises a solid electrolyte layer including a conductive polymer that covers at least a portion of the dielectric layer, and a cathode lead-out layer that covers at least a portion of the solid electrolyte layer. An electrolytic capacitor having a solid electrolyte layer including a conductive polymer is also referred to as a solid electrolytic capacitor.
[0003] Patent document 1 proposes a method for manufacturing a solid electrolytic capacitor, which is a method for manufacturing a solid electrolytic capacitor having a capacitor element having a dielectric layer and a solid electrolyte layer, wherein the formation of the aforementioned solid electrolyte layer has the following steps in sequence: a first step, applying a first conductive polymer solution in which fine particles of a conductive polymer are dispersed, and drying to form a first conductive polymer layer; a second step, applying a covering solution containing at least one selected from aromatic sulfonic acids or salts thereof to the first conductive polymer layer, and drying, wherein the aromatic sulfonic acid has a carboxyl group and a hydroxyl group, or two carboxyl groups in one molecule; and a third step, applying a second conductive polymer solution in which fine particles of a conductive polymer are dispersed, and drying to form a second conductive polymer layer.
[0004] Patent document 2 proposes an electrolytic capacitor comprising at least one capacitor element, the capacitor element comprising: a sheet-shaped anode body having an anode lead-out portion including a first end and a cathode forming portion including a second end; a dielectric layer formed on a surface of at least the cathode forming portion of the anode body; and a cathode portion covering at least a portion of the dielectric layer, the cathode portion comprising a solid electrolyte layer comprising a conductive polymer covering at least a portion of the dielectric layer, wherein at any position of a portion on the first end side of the cathode portion, in a cross section perpendicular to a direction from the first end toward the second end of the capacitor element, a ratio of a thickness T1 of the solid electrolyte layer formed at a corner of the anode body to a thickness T2 of the solid electrolyte layer formed at a central portion of a main surface of the anode body: T1 / T2 is greater than or equal to 0.8 and less than or equal to 1.7.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2014 / 087617
[0008] Patent Document 2: International Publication No. 2021 / 132223 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] Ensures high withstand voltage of electrolytic capacitors and suppresses leakage current.
[0011] Solutions for solving problems
[0012] One scheme of the present disclosure relates to an electrolytic capacitor, which includes at least one capacitor element, wherein the capacitor element includes: an anode body including a porous portion in the surface layer; a dielectric layer covering at least a portion of the surface of the anode body; and a solid electrolyte layer covering at least a portion of the dielectric layer. The anode body has a first end and a second end opposite to the first end. The solid electrolyte layer is formed on a portion of the anode body having the dielectric layer including the second end, and has a first portion arranged in the voids of the porous portion and a second portion arranged on the outside of the main surface of the anode body having the dielectric layer. The second portion includes n or more conductive polymer layers on the main surface of the anode body having the dielectric layer, satisfying the following relationship.
[0013] 18.0μm≤Tt≤50.0μm
[0014] 9.0μm≤Tt / n≤12.5μm
[0015] Here, n is an integer greater than or equal to 2, and Tt is a thickness of the second portion on one main surface of the anode body having the dielectric layer at the second end portion.
[0016] Another scheme of the present disclosure relates to a method for manufacturing an electrolytic capacitor. The aforementioned manufacturing method includes: a first step of preparing an anode body including a porous portion on the surface layer and having a first end and a second end opposite to the aforementioned first end; a second step of forming a dielectric layer on at least a portion of the surface of the aforementioned anode body; and a third step of forming a solid electrolyte layer covering at least a portion of the aforementioned dielectric layer. The aforementioned solid electrolyte layer is formed on a portion of the aforementioned anode body including the aforementioned second end and includes a first portion arranged in the voids of the aforementioned porous portion and a second portion arranged on the outside of the main surface of the aforementioned anode body including the aforementioned dielectric layer. The aforementioned second portion includes n or more conductive polymer layers on the aforementioned main surface of the aforementioned anode body including the aforementioned dielectric layer. The third step includes: a sub-step A of treating the portion of the anode body including the second end with the dielectric layer using a first treatment solution containing a first conductive polymer or a precursor thereof; a sub-step B of treating the portion of the anode body including the second end with a second treatment solution containing at least a cationic agent after the sub-step A; a sub-step C of treating the portion of the anode body including the second end with a third treatment solution containing a second conductive polymer and a water-soluble polymer after the sub-step B; and a sub-step D of repeating the sub-steps B and C. In the third step, the solid electrolyte layer is formed in a manner satisfying the following relationship.
[0017] 18.0μm≤Tt≤45.0μm
[0018] 9.0μm≤Tt / n≤12.5μm
[0019] Here, n is an integer greater than or equal to 2, and Tt is a thickness of the second portion on the main surface of the anode body having the dielectric layer at the second end portion.
[0020] Effects of the Invention
[0021] The present disclosure provides an electrolytic capacitor capable of ensuring high withstand voltage and suppressing leakage current. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 1 is a schematic cross-sectional view of an electrolytic capacitor according to an embodiment of the present disclosure.
[0023] Description of Reference Numerals
[0024] 1: Electrolytic capacitor
[0025] 2: Capacitor element
[0026] 3: Resin outer body
[0027] 4: Anode lead terminal
[0028] 5: Cathode lead terminal
[0029] 6: Anode
[0030] 7: Dielectric layer
[0031] 8: Cathode
[0032] 9: Solid electrolyte layer
[0033] 10: Cathode lead layer
[0034] 11: Layer 1
[0035] 12: Layer 2
[0036] 13: Separation section (insulation area)
[0037] 14: Adhesive layer DETAILED DESCRIPTION
[0038] For electrolytic capacitors with solid electrolyte layers, when the solid electrolyte layer has a certain thickness, it can be expected that the leakage current will be reduced and high withstand voltage will be obtained compared to the case where the thickness is small. However, if the thickness of the solid electrolyte is further increased, although higher withstand voltage will be obtained, thermal shrinkage will occur during the formation of the solid electrolyte, and defects will be generated in the dielectric layer due to the stress associated with this, and the leakage current will increase.
[0039] The solid electrolyte layer is formed, for example, as follows: the anode body having a dielectric layer is coated with a treatment solution containing a conductive polymer and then dried, or the precursor (monomer, etc.) is polymerized after being coated with a treatment solution containing a conductive polymer precursor, thereby forming a solid electrolyte layer. If the coating and drying (or polymerization) of such a treatment solution are repeated many times, the conductive polymer is stacked in a multi-layered manner, which can increase the thickness of the solid electrolyte layer as a whole. However, due to the interface resistance generated between adjacent layers of conductive polymers, the conductivity of the solid electrolyte layer is reduced, and the equivalent series resistance (ESR) in the electrolytic capacitor is increased. In addition, if the coating and drying (or polymerization) of the treatment solution are repeated many times, the number of processes increases, which is disadvantageous in terms of cost.
[0040] (Technology 1)
[0041] An electrolytic capacitor of one embodiment of the present disclosure includes at least one capacitor element, the capacitor element including: an anode body including a porous portion in the surface layer; a dielectric layer covering at least a portion of the surface of the anode body; and a solid electrolyte layer covering at least a portion of the dielectric layer. The anode body has a first end and a second end opposite to the first end. The solid electrolyte layer is formed on a portion of the anode body including the dielectric layer including the second end, and has a first portion arranged in the voids of the porous portion and a second portion arranged on the outside of the main surface of the anode body including the dielectric layer. The second portion includes n or more conductive polymer layers on the main surface of the anode body including the dielectric layer, satisfying the following relationship.
[0042] 18.0μm≤Tt≤50.0μm
[0043] 9.0μm≤Tt / n≤12.5μm
[0044] Here, n is an integer greater than 2, and Tt is the thickness of the second portion on one main surface of the anode body having the dielectric layer at the second end. In this specification, the conductive polymer layer mainly included in the first portion is sometimes referred to as the first conductive polymer layer, and the conductive polymer layer mainly included in the second portion is sometimes referred to as the second conductive polymer layer.
[0045] According to the electrolytic capacitor disclosed in the present invention, as described above, the thickness Tt of the second part on the main surface of the solid electrolyte layer is within a specific range, and the ratio Tt / n is within a specific range, and n is an integer greater than 2. Thus, leakage current can be suppressed and high withstand voltage can be obtained. By having a larger ratio Tt / n, even if the number of layers n of the second conductive polymer layer is small, the thickness Tt can be made larger. Therefore, by the heat shrinkage of the second conductive polymer layer accompanying the heating treatment (drying, etc.) when forming the second part, the stress applied to the dielectric layer can be reduced, and leakage current can be suppressed. In addition, it is believed that the high withstand voltage is due to the large thickness Tt and the ratio Tt / n. And, for the electrolytic capacitor disclosed in the present invention, low ESR can be ensured. It is believed that this is because the total value of the interface resistance between the second conductive polymer layers in the second part can be reduced by having a small number of layers n of the second conductive polymer layer, and the high conductivity of the second part can be ensured.
[0046] It should be noted that the ratio Tt / n can be roughly regarded as the average thickness of one conductive polymer layer in the second portion.
[0047] (Technique 2)
[0048] In the above (Technique 1), n may be equal to or less than 4. In this case, the total value of the interface resistance between the second conductive polymer layers can be further reduced, so that a lower ESR can be easily obtained.
[0049] (Technique 3)
[0050] In the above (Technique 1) or (Technique 2), 20.0μm<Tt can be satisfied. In this case, it is easy to ensure higher voltage resistance. In addition, if the thickness Tt is large, defects are generated in the dielectric layer due to the stress associated with thermal shrinkage, and the leakage current tends to become significant. However, in the present disclosure, by setting the thickness Tt / n and the number of the second conductive polymer layer to a specific range, even if the thickness Tt is large, 20μm<Tt≤45.0μm, the leakage current can be suppressed to a low level.
[0051] (Technique 4)
[0052] In any one of the above (Technique 1) to (Technique 3), the aforementioned second part may contain a water-soluble polymer. The weight average molecular weight (Mw) of the aforementioned water-soluble polymer may be greater than 50,000 and less than 800,000. By including a water-soluble polymer in the second part, it is easy to form a conductive polymer layer with a relatively uniform thickness, thereby obtaining a higher voltage resistance. When the weight average molecular weight (Mw) of the water-soluble polymer is within the above range, even if the number of layers n is small, the thickness Tt and the ratio Tt / n can be easily adjusted to the above range compared to the case outside the above range. Thus, a higher voltage resistance is obtained. In addition, it is easy to further reduce the total value of the interface resistance between adjacent second conductive polymer layers. Since it is possible to ensure a higher conductivity of the second part as a whole, the ESR can be further reduced. Since the number of layers n can be reduced, it is easy to reduce the stress applied to the dielectric layer due to the thermal shrinkage of the second part, and it is easy to further reduce the leakage current. When the weight average molecular weight (Mw) of the water-soluble polymer is 50,000 or more and 800,000 or less, it is easy to form a second conductive polymer layer having relatively uniform film quality and thickness.
[0053] (Technique 5)
[0054] In the above (Technique 4), the content of the water-soluble polymer in the second part can be 10% by mass or more and 20% by mass or less. In this case, it is easy to obtain the effect achieved by the water-soluble polymer. Therefore, higher voltage resistance and lower ESR can be ensured, and leakage current can be further reduced.
[0055] (Technique 6)
[0056] In any of the above (Technique 1) to (Technique 5), the aforementioned second part may include at least one continuous or discontinuous layer sandwiched between adjacent conductive polymer layers (specifically, the second conductive polymer layer) in the aforementioned n or more conductive polymer layers. The aforementioned continuous or discontinuous layer may contain at least a cationic agent. By including such a layer in the second part, it is easy to form a second conductive polymer layer with a larger thickness on the layer, and it is easy to reduce n. As a result, it is easy to maintain the high conductivity of the second part, and therefore it is easy to obtain a lower ESR.
[0057] (Technique 7)
[0058] Another method for manufacturing an electrolytic capacitor of the present disclosure includes: a first step of preparing an anode body including a porous portion on the surface layer and having a first end and a second end opposite to the first end; a second step of forming a dielectric layer on at least a portion of the surface of the anode body; and a third step of forming a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer is formed on a portion of the anode body including the second end and having a first portion disposed in a void in the porous portion and a second portion disposed on the outside of a main surface of the anode body including the dielectric layer. The second portion includes n or more conductive polymer layers on the main surface of the anode body including the dielectric layer. The third step includes: a sub-step A of treating the portion of the anode body including the second end with the dielectric layer using a first treatment solution containing a first conductive polymer or a precursor thereof; a sub-step B of treating the portion of the anode body including the second end with a second treatment solution containing at least a cationic agent after the sub-step A; a sub-step C of treating the portion of the anode body including the second end with a third treatment solution containing a second conductive polymer and a water-soluble polymer after the sub-step B; and a sub-step D of repeating the sub-steps B and C. In the third step, the solid electrolyte layer is formed in a manner satisfying the following relationship.
[0059] 18.0μm≤Tt≤45.0μm
[0060] 9.0μm≤Tt / n≤12.5μm
[0061] Here, n is an integer greater than or equal to 2, and Tt is a thickness of the second portion on the main surface of the anode body having the dielectric layer at the second end portion.
[0062] In the electrolytic capacitor obtained by the above manufacturing method, the thickness Tt of the second portion is within a specific range, and the ratio Tt / n is within a specific range, and n ≥ 2. Therefore, as described above, in the electrolytic capacitor, ESR is suppressed to be low, leakage current is suppressed, and high withstand voltage is obtained.
[0063] (Technology 8)
[0064] Regarding the above (Technique 7), in the above sub-step D, the above sub-step B and the above sub-step C may be repeated (n-1) times. In this case, it is further easy to adjust the thickness Tt of the second portion to the above range, and it is easy to obtain high withstand voltage.
[0065] (Technique 9)
[0066] In the above (Technique 7) or (Technique 8), the above n may be 2 or more and 4 or less. In this case, the total value of the interface resistance between the second conductive polymer layers can be further reduced, so that a lower ESR can be easily obtained.
[0067] (Technology 10)
[0068] In any one of the above (Technique 7) to (Technique 9), the weight average molecular weight (Mw) of the water-soluble polymer may be greater than 50,000 and less than 800,000. In this case, even if the number of layers n is small, the thickness Tt and the ratio Tt / n can be easily adjusted to the above range. Thus, high voltage resistance is obtained, and leakage current can be further suppressed. In addition, since high conductivity is obtained in the second part, ESR can be further reduced.
[0069] (Technology 11)
[0070] In any one of the above (Technique 7) to (Technique 10), the concentration of the water-soluble polymer in the third treatment liquid may be 1% by mass or more and 15% by mass or less. Thus, the second part contains the water-soluble polymer at an appropriate content, thereby ensuring higher withstand voltage and low ESR, and further reducing leakage current.
[0071] The following is a more specific description of the electrolytic capacitor and its manufacturing method of the present disclosure including the above-mentioned (Technique 1) to (Technique 11). At least one of the components selected from the following can be combined with at least one of the above-mentioned (Technique 1) to (Technique 11) of the electrolytic capacitor or its manufacturing method of the present disclosure as long as it can be combined technically.
[0072] [Electrolytic capacitors]
[0073] An electrolytic capacitor includes at least one capacitor element.
[0074] (Capacitor Components)
[0075] The capacitor element includes an anode body, a dielectric layer covering at least a portion of the surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer. The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer.
[0076] (Anode)
[0077] The anode body may include, for example, a valve metal, an alloy containing a valve metal, and a compound (intermetallic compound, etc.) containing a valve metal. These materials may be used alone or in combination of two or more. Examples of valve metals include aluminum, tantalum, niobium, and titanium.
[0078] The anode body may be a foil (anode foil) of the above-mentioned material. The anode body may be a formed body (porous formed body) of particles of the above-mentioned material or a sintered body (porous sintered body) thereof.
[0079] The anode body has a first end and a second end on the opposite side of the first end. The anode body includes, for example, an anode lead-out portion including the first end and a cathode forming portion including the second end. A cathode portion including a solid electrolyte layer is formed on the surface of a portion on the second end side of the anode body (specifically, the cathode forming portion). The anode lead-out portion is used, for example, to electrically connect to an external electrode on the anode side. An anode lead terminal may also be connected to the anode lead-out portion.
[0080] The anode body includes a porous portion at least on the surface. The porous portion includes many fine voids. Through the porous portion, the anode body has a fine concavo-convex shape at least on the surface, the surface area becomes larger, and a high capacity is obtained. The porous portion can be formed on a part of the surface layer of the anode body, and can also be formed on the entire surface layer. In the case where the anode body is an anode foil, the porous portion can be formed on at least the surface layer of the cathode forming portion, or can be formed on at least a part of the surface layer of the anode lead-out portion in addition to being formed on the surface layer of the cathode forming portion. In the case where the anode body is a porous formed body or a porous sintered body, the entire anode body can constitute the porous portion.
[0081] When the anode body is an anode foil, the porous portion is formed by roughening the surface of at least a portion of a substrate (eg, metal foil) containing a valve metal corresponding to the cathode forming portion. The roughening can be performed by etching or the like.
[0082] For example, an anode body in a sheet or rectangular shape usually has six faces that determine the shape of the anode body. Sometimes, the faces (usually a pair of faces) that occupy the largest area among these faces are called main faces, and the faces other than the main faces are called end faces. For example, when the anode body is an anode foil, it has a pair of main faces that occupy most of the area of the anode foil and an end face that exists between the pair of main faces. Even when there is a cutout or unevenness in a part of the anode body, sometimes, according to the above, the faces (usually a pair of faces) that occupy the largest area are called main faces, and the faces other than the main faces are called end faces.
[0083] In this specification, the direction from the first end toward the second end when the anode body (anode foil, etc.) is flat is sometimes referred to as the length direction of the anode body. The direction from the first end side toward the second end side refers to the direction parallel to the straight line connecting the center of the end face of the first end and the center of the end face of the second end. This direction is sometimes referred to as the length direction of the anode body or capacitor element. In addition, the direction perpendicular to the length direction and thickness direction of the anode body (or capacitor element) is sometimes referred to as the width direction of the anode body (or capacitor element).
[0084] (Dielectric layer)
[0085] The dielectric layer is an insulating layer that functions as a dielectric and is formed of a material that functions as a dielectric.
[0086] For a material that functions as a dielectric, the dielectric layer includes, for example, a metal oxide. For example, when the anode body includes tantalum as a valve metal, the dielectric layer includes Ta2O5. When the anode body includes aluminum as a valve metal, the dielectric layer includes Al2O3. However, the dielectric layer is not limited to this, and may be any material as long as it functions as a dielectric.
[0087] The dielectric layer includes the inner wall surfaces of the pores of the porous portion and is formed along the inner wall surfaces of the pores and depressions (pits) on the surface of the anode body. The surface of the dielectric layer has fine irregularities depending on the shape of the surface of the porous portion.
[0088] (Cathode)
[0089] The cathode portion at least includes a solid electrolyte layer covering at least a portion of the dielectric layer. The portion of the solid electrolyte layer on the second end side of the anode body (in other words, the cathode forming portion) is formed with the aid of the dielectric layer. The cathode portion generally includes a solid electrolyte layer covering at least a portion of the dielectric layer and a cathode lead layer covering at least a portion of the solid electrolyte layer. The solid electrolyte layer and the cathode lead layer are described below.
[0090] (Solid electrolyte layer)
[0091] The solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer. The solid electrolyte layer has a first portion arranged in the voids of the porous portion and a second portion arranged outside the main surface of the anode body having the dielectric layer.
[0092] The first part and the second part of the solid electrolyte layer are respectively composed of a conductive polymer (a conjugated polymer and a dopant, etc.). The first part and the second part may also respectively include a conductive polymer layer. The solid electrolyte layer or the conductive polymer layer may further include an additive as needed.
[0093] As conjugated polymers, known conjugated polymers used in solid electrolytic capacitors, such as π-conjugated polymers, can be listed. As conjugated polymers, polymers with basic skeletons such as polypyrrole, polythiophene, polyaniline, polyfuran, polyacetylene, polyphenylene, polyphenylene vinylene, polyphenylene and polythiophene vinylene can be listed. Among them, polymers with polypyrrole, polythiophene or polyaniline as basic skeletons are preferred. The above-mentioned polymers only need to contain at least one monomer unit constituting the basic skeleton. The monomer unit also includes a monomer unit having a substituent. The above-mentioned polymers also include homopolymers and copolymers of two or more monomers. For example, polythiophene includes poly (3,4-ethylenedioxythiophene) (PEDOT) and the like.
[0094] As the substituent, an alkyl group (such as a methyl group or an ethyl group) is preferred. 1-4 Alkyl, etc.), alkoxy (methoxy, ethoxy, etc. C 1-4 alkoxy, etc.), hydroxyl, hydroxyalkyl (hydroxymethyl, etc. hydroxy C 1-4 In the case where the pyrrole compound, the thiophene compound and the aniline compound each have two or more substituents, the substituents may be the same or different.
[0095] The first part and the second part may each contain one type of conjugated polymer, or may contain two or more types in combination. The first part and the second part may each contain one type of dopant, or may contain two or more types in combination.
[0096] The weight average molecular weight (Mw) of the conjugated polymer is not particularly limited, and is, for example, 1,000 or more and 1,000,000 or less.
[0097] In this specification, the weight average molecular weight (Mw) is a value in terms of polystyrene measured by gel permeation chromatography (GPC). In general, GPC is measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as a mobile phase.
[0098] The dopant may be at least one selected from the group consisting of anions and polyanions.
[0099] As anions, for example, sulfate ions, nitrate ions, phosphate ions, borate ions, organic sulfonate ions, carboxylate ions, etc. can be listed, without particular limitation. In the case where the dopant is an anion, for example, a compound with a lower molecular weight that generates anions is used. As a dopant that generates sulfonate ions, sulfonic acid compounds such as aromatic sulfonic acid compounds can be listed. As aromatic sulfonic acid compounds, benzenesulfonic acid, p-toluenesulfonic acid and naphthalenesulfonic acid can be listed. The sulfonic acid compound can be used alone or in combination of two or more.
[0100] As specific examples of polyanions, polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly (2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, etc. can be listed. They can be used alone or in combination of two or more. In addition, they can be polymers of single monomers or copolymers of two or more monomers. Among them, preferably, the polyanion is derived from polystyrene sulfonic acid.
[0101] The amount of the dopant contained in each of the first part and the second part is, for example, 10 parts by mass or more and 1000 parts by mass or less, or 20 parts by mass or more and 500 parts by mass or less, based on 100 parts by mass of the conjugated polymer.
[0102] In each of the first and second parts, the anionic group of the dopant may be included in a free form, an anionic form, or a salt form, or may be included in a form bonded to or interacting with a conjugated polymer. In this specification, all of these forms are included, and sometimes referred to as "anionic group", "sulfonic acid group" or "carboxyl group" or the like.
[0103] The first part and the second part can each contain a water-soluble polymer, or can contain two or more in combination. The treatment liquid containing water-soluble polymers has a tendency to increase in viscosity, so it is preferred that the first part does not contain water-soluble polymers, or even if it contains water-soluble polymers, the content of water-soluble polymers is small. The content of water-soluble polymers in the first part can be, for example, less than 5% by mass or less than 1% by mass. On the other hand, when the second part contains water-soluble polymers, the withstand voltage is further improved, and the leakage current can be further suppressed, so it is preferred.
[0104] As water-soluble polymers, for example, water-soluble polymer compounds having hydrophilic groups in the main chain or side chain can be cited. As the hydrophilic group possessed by the water-soluble polymer, polyoxyalkylene chains, hydroxyl groups, acid groups (carboxyl groups, sulfonic acid groups, etc.) and the like can be cited. As water-soluble polymers, components with lower electron-withdrawing properties than dopants are generally used. As such water-soluble polymers, for example, water-soluble polymers having at least one hydrophilic group (first hydrophilic group) selected from the group consisting of carboxyl groups, hydroxyl groups and polyoxyalkylene chains can be cited. A water-soluble polymer having a first hydrophilic group and a sulfonic acid group can be used, and a water-soluble polymer not containing a sulfonic acid group can also be used. As polyoxyalkylene chains, polyoxyC 2-3 Alkylene chain, etc. The polyoxyalkylene chain may contain at least a polyoxyethylene chain. As the water-soluble polymer, for example, at least one selected from the group consisting of polyalkylene glycol compounds, water-soluble polyurethanes, water-soluble polyamides, water-soluble polyimides, water-soluble acrylic resins and polyvinyl alcohols can be cited. The water-soluble polymer preferably has at least a plurality of carboxyl groups. As such a water-soluble polymer, polymer-type polycarboxylic acids, resins introduced with a plurality of carboxyl groups (water-soluble polyurethane resins, water-soluble polyamides, water-soluble polyimides, water-soluble acrylic resins, etc.) and the like can be cited.
[0105] Water-soluble acrylic resins, for example, also include acrylic polymer polycarboxylic acids. As such polymer polycarboxylic acids, for example, polyacrylic acid, polymethacrylic acid, copolymers using at least one of acrylic acid and methacrylic acid (acrylic acid-methacrylic acid copolymers, copolymers of at least one selected from the group consisting of acrylic acid and methacrylic acid and other copolymerizable monomers, etc.) can be cited. As other copolymerizable monomers, for example, acrylates (alkyl esters, hydroxyalkyl esters, etc.), methacrylates (alkyl esters, hydroxyalkyl esters, etc.), vinyl compounds (acrylonitrile, olefins, aromatic vinyl compounds, etc.), polycarboxylic acids (maleic acid, fumaric acid, etc.) having polymerizable unsaturated bonds or their anhydrides can be cited. The copolymer can include one monomer unit derived from other copolymerizable monomers, or it can include two or more.
[0106] The acid groups such as carboxyl and sulfonic acid groups possessed by the water-soluble polymer can be included in the solid electrolyte layer in the form of free, anion or salt as in the case of the dopant. In addition, a part of the acid group can also be included in the solid electrolyte layer in the form of bonding or interacting with the conjugated polymer. In this specification, the carboxyl group including all forms is sometimes referred to as "carboxyl group", and the sulfonic acid group including all forms is sometimes referred to as "sulfonic acid group".
[0107] The weight average molecular weight (Mw) of the water-soluble polymer is, for example, 1,000 to 1,000,000, or 10,000 to 800,000, and preferably 50,000 to 800,000.
[0108] In the solid electrolyte layer, at least one continuous or discontinuous layer can be sandwiched between adjacent conductive polymer layers. The continuous or discontinuous layer can contain at least a cationic agent. The continuous or discontinuous layer can contain a cationic agent and an anionic agent. The continuous or discontinuous layer can also contain a surfactant as needed. Here, as a surfactant, a component different from a cationic agent and an anionic agent is used. More specifically, the continuous or discontinuous layer is sandwiched between the first adjacent conductive polymer layer, between the first conductive polymer layer and the second conductive polymer layer, and between the second adjacent conductive polymer layer. By arranging such a continuous or discontinuous layer, it is easy to attach a large amount of conductive polymers on the conductive polymer layer, and the film-forming property of the conductive polymer layer can be improved. Especially when the second part contains such a continuous or discontinuous layer, even if the second conductive polymer layer number n is less, the thickness Tt and the ratio Tt / n can be increased, and it is easy to adjust to the above-mentioned range. When an anionic agent is used, the dissociation property of the cationic agent in the treatment liquid (second treatment liquid) for forming a continuous or discontinuous layer can be increased, and the film-forming property of the conductive polymer layer can be further improved.
[0109] The cationic agent has a cationic group. The cationic agent is not particularly limited as long as it can generate cations in a dissociated state. As the cationic agent, for example, organic compounds (organic bases, etc.) containing N elements, metal compounds (inorganic bases such as metal hydroxides, etc.) can be listed. The cationic group of the cationic agent as an organic compound is preferably an amino group (primary amino group, secondary amino group and tertiary amino group, etc.) and a quaternary ammonium group. Such a cationic group also includes salts of amino groups and salts of quaternary ammonium groups, etc. The first part and the second part can each contain one cationic agent, or can contain two or more cationic agents.
[0110] Specific examples of the cationic agent include diamines (1,4-diaminobutane, 1,6-diaminohexane, 1,8-diaminooctane, 1,10-diaminodecane, diaminocyclohexane, diaminobenzene, diaminonaphthalene, etc.) and tertiary amines (N,N-dimethylhexylamine, N,N-dimethyloctylamine, N,N-diethyloctylamine, etc.). However, the cationic agent is not limited to these.
[0111] The first part and the second part may each contain a cationic agent in the form of an amine compound, a cation corresponding to the amine compound, a quaternary ammonium compound, and a salt of a cation. For example, in each of the first part and the second part, the cationic agent may form a salt with an anionic agent or may interact with a dopant.
[0112] The anionic agent has an anionic group. As the anionic agent, for example, at least one selected from the group consisting of anions and polyanions exemplified as dopants of the first conductive polymer and the second conductive polymer can be used. As the anionic agent, an anionic agent having lower electron-withdrawing property than the dopant of each conductive polymer can be used. The first part and the second part can each contain one anionic agent, or can contain two or more anionic agents.
[0113] In each of the first part and the second part, the anionic group of the anionic agent may be contained in any form selected from the above-mentioned anionic groups, anions corresponding to the above-mentioned anionic groups, and salts of anions.
[0114] Examples of the anionic agent include sulfonic acid compounds (methanesulfonic acid, benzenesulfonic acid, styrenesulfonic acid, etc.), phosphonic acid compounds (phenylphosphonic acid, etc.), carboxylic acids (salicylic acid, phthalic acid, etc.), hydroxyalkyl esters of carboxylic acids (hydroxyethyl acrylate, hydroxyethyl methacrylate, etc.), and phenolic compounds. In addition, anionic agents having two or more anionic groups may also be used. Examples of such anionic agents include sulfosuccinic acid, sulfobenzoic acid, sulfosalicylic acid, disulfosalicylic acid, sulfophthalic acid, sulfoisophthalic acid, sulfoterephthalic acid, naphtholsulfonic acid, 2-(dihydroxyphosphinyloxy)acrylic acid, phosphonoacrylic acid, and 2-methyl-3-phosphonoacrylic acid.
[0115] A polymer type anionic agent may also be used. Examples of such anionic agents include acidic phosphoryloxy polyoxyalkylene glycol monoacrylates of carboxylic acids such as acidic phosphoryloxy ethyl acrylate and acidic phosphoryloxy ethyl methacrylate (acidic phosphoryloxy polyoxyethylene glycol mono(meth)acrylate (P(=O)(OH)2-(O-CH2CH2) n -OC(=O)-CR=CH2) (n is an integer of 2 to 10, R is a hydrogen atom or a methyl group), aliphatic phosphonic acid (vinyl phosphonic acid, etc.), etc.
[0116] The surfactant contained in the continuous or discontinuous layer can be any one of a nonionic surfactant and an ionic surfactant. Ionic surfactants include cationic surfactants, anionic surfactants and amphoteric surfactants. The continuous or discontinuous layer can contain one surfactant or a combination of two or more surfactants.
[0117] The first part and the second part can each further include at least one of the group consisting of known conductive materials other than known additives and conductive polymers as required. As the conductive material, at least one of the group consisting of conductive inorganic materials such as manganese dioxide and TCNQ complex salts can be listed. In addition, a layer that improves adhesion can also be sandwiched between the dielectric layer and the first part (or the first conductive polymer layer).
[0118] (Part 1)
[0119] The conductive polymer (first conductive polymer) included in the first portion is formed using, for example, a treatment solution (first treatment solution) containing the first conductive polymer or its precursor. The first conductive polymer is arranged in the voids of the porous portion of the anode body so as to cover at least a portion of the dielectric layer.
[0120] In the first portion, the first conductive polymer layer may be a single layer or multiple layers. When the first portion is composed of multiple first conductive polymer layers, the first conductive polymer contained in each layer may be the same or different.
[0121] It should be noted that when the second part is formed using a treatment solution (second treatment solution) containing a second conductive polymer, the second conductive polymer sometimes enters the gaps in the porous part of the anode body having a dielectric layer. Therefore, the second conductive polymer may also be included in the first part. In addition, sometimes the first conductive polymer is attached to the surface of the convex part of the porous part of the anode body having a dielectric layer, and the second conductive polymer layer is stacked on the attached first conductive polymer. Therefore, sometimes the first conductive polymer is included in the second part.
[0122] (Part 2)
[0123] The second part includes n or more conductive polymer layers (second conductive polymer layer) on a main surface of the anode body having a dielectric layer. n is an integer greater than 2. When n is less than 2, it is difficult to adjust the thickness Tt and the ratio Tt / n of the second part to a specified range. n can be less than 5 or less than 4. In the present disclosure, even if n is less, a certain degree of thickness Tt of the second part can be ensured. As a result, high voltage resistance can be obtained while ensuring low ESR, and leakage current can be suppressed.
[0124] In each second conductive polymer layer included in the second portion, the types, compositions, contents, and the like of the conductive polymer, additives, and the like may be the same or different.
[0125] The thickness Tt of the second part satisfies 18.0μm≤Tt≤50.0μm. Tt is preferably Tt>20.0μm, and more preferably Tt≥22.0μm. By having Tt in such a range, high voltage resistance is obtained. Even if the number of layers n is small, by having the thickness Tt in such a range, the total value of the interface resistance between the second conductive polymer layers in the second part can be reduced, and the ESR can be suppressed to a low level. If the thickness Tt exceeds 50.0, defects are likely to occur in the dielectric layer due to the stress associated with the thermal shrinkage during the formation of the second part, and the leakage current is likely to become significant. In contrast, by having the thickness Tt be less than 50.0μm, the leakage current can be reduced. From the viewpoint of further suppressing the leakage current, the thickness Tt can be less than 45.0μm.
[0126] The thickness Tt may be 18.0 μm ≤ Tt ≤ 50.0 μm (or 45.0 μm), 20.0 μm < Tt ≤ 50.0 μm (or 45.0 μm), or 22.0 μm ≤ Tt ≤ 50.0 μm (or 45.0 μm).
[0127] The ratio Tt / n satisfies 9.0μm≤Tt / n≤12.5μm. When Tt / n is less than 9.0μm, in order to make the thickness Tt within the above range, it is necessary to increase the number of layers n, the total value of the interface resistance becomes larger, and thus the ESR becomes larger. The ratio Tt / n can be Tt / n≥9.5μm or Tt / n≥9.8μm. By making the ratio Tt / n within such a range, the ESR can be further reduced. The ratio Tt / n can be Tt / n≤12.0μm or Tt / n≤11.5μm. When the ratio Tt / n is within such a range, it is easy to adjust the thickness Tt to the above range, and it is easy to obtain a higher effect.
[0128] The thickness Tt of the second portion and the number n of the second conductive polymer layers are determined from the Raman spectrum of a cross section parallel to the longitudinal direction of the anode body and perpendicular to the thickness direction (the stacking direction of the second conductive polymer layers) in the electrolytic capacitor or capacitor element.
[0129] In the determination of Raman spectra, samples collected according to the following steps can be used. First, an electrolytic capacitor or a capacitor element is embedded in a curable resin and the curable resin is cured. The cured product is ground or processed by a cross-section polisher to expose a cross section parallel to the length direction of the capacitor element (or anode body) and perpendicular to the thickness direction (the stacking direction of the second conductive polymer layer) in the center of the width direction of the capacitor element (or anode body). In this way, a sample for measurement is obtained. In the exposed cross section of the sample, the Raman spectrum is measured for at least the portion on the second end side of the second portion.
[0130] In this specification, the Raman spectrum in the second part is measured under the following conditions for a solid electrolyte in a cross section of a porous portion present at a predetermined position of a capacitor element.
[0131] Raman spectrometer: NanoPhoton RamanFORCE PAV
[0132] Diffraction grating: 300gr / mm
[0133] Measurement wave number range: 200cm -1 Above and 4500cm -1 the following
[0134] Temperature: 25℃
[0135] Laser wavelength: 532nm
[0136] Laser intensity: 1600W / cm 2
[0137] Exposure time: 8 seconds
[0138] Total times: 16 times
[0139] Coloration of conductive polymers: When the conjugated polymer is PEDOT, the color of the conductive polymer is 1415 cm -1 Above and 1460cm -1 The average intensity I1 in the range below 1100 cm -1 Over 1170cm -1 The Raman spectrum is colored in such a way that the ratio of the average intensity I2 in the following range: I1 / I2 is greater than 1.0 and less than 2.0. The portion with an I1 / I2 ratio of 1.7 or more is judged to be PEDOT. It should be noted that the average intensity I1 is the average intensity of the wavenumber range covering the characteristic peak of the conjugated polymer, and the average intensity I2 is the average intensity of the wavenumber range equivalent to the baseline of the aforementioned peak. In the case of other conjugated polymers, the conductive polymer portion is also colored according to the case of PEDOT.
[0140] In the Raman spectrum, the thickness of the solid electrolyte layer (second portion) formed on one main surface of the anode body is measured at the second end of the anode body (more specifically, the position of the endmost portion of the second end). The thickness of the solid electrolyte layer (second portion) formed on the main surface on the opposite side is measured. Then, these thicknesses are summed up and averaged to obtain the thickness Tt (unit: μm) of the second portion.
[0141] In the Raman spectrum, for example, the second conductive polymer layer in a layered state is confirmed by the coloring. The number of second conductive polymer layers formed on one main surface of the anode body is measured to find n. The ratio Tt / n (unit: μm) is found by dividing the thickness Tt by n.
[0142] The second part preferably contains a water-soluble polymer as described above. In particular, when the second part contains a water-soluble polymer having a weight average molecular weight (Mw) of 50,000 or more and 800,000 or less, even if the number of layers n of the second conductive polymer layer is small, it is easy to adjust the thickness Tt and the ratio Tt / n to the above range. Thus, a more excellent effect is obtained in terms of ESR reduction, leakage current suppression, and voltage resistance improvement.
[0143] The content of the water-soluble polymer in the second part can be 5% by mass or more and 20% by mass or less, or 10% by mass or more and 20% by mass or less. When the content of the water-soluble polymer is within such a range, a higher withstand voltage can be ensured, and leakage current can be further suppressed. Since it is easy to ensure high conductivity of the second part, it is beneficial to further reduce ESR.
[0144] The content of water-soluble polymers in the second part can be determined using a sample of the second part (hereinafter referred to as sample A) collected from the cross section of the sample. More specifically, the second part is scraped from the cross section, a predetermined amount of sample A is collected, and the mass is measured. The water-soluble polymer is extracted from sample A using water at 20°C to 40°C. The extract is concentrated and the water-soluble polymer is identified by liquid chromatography-mass spectrometry (LC-MS) or gas chromatography-mass spectrometry (GC-MS). The concentration of the water-soluble polymer in the extract is determined using a standard curve method. The content (mass %) of the water-soluble polymer in the second part is determined from the concentration and the mass of sample A. The above-mentioned sample is prepared as follows: an electrolytic capacitor or a capacitor element is embedded in an acrylic resin, and the cross section is exposed by cutting in the center of the width direction of the capacitor element in a direction parallel to the length direction, and grinding is performed to prepare the above-mentioned sample. It should be noted that the content of the water-soluble polymer in the first part is also determined according to the content in the second part.
[0145] (Cathode extraction layer)
[0146] The cathode lead layer only needs to include at least a first layer that is in contact with the solid electrolyte layer and covers at least a portion of the solid electrolyte layer, and may include the first layer and a second layer that covers at least a portion of the first layer.
[0147] As the first layer, for example, a layer containing conductive particles, a metal foil, etc. can be cited. As the conductive particles, for example, at least one selected from conductive carbon and metal powder can be cited. The cathode portion (more specifically, the cathode lead layer) can include a layer containing metal powder (metal particle-containing layer, etc.). The cathode lead layer can be composed of, for example, a layer containing conductive carbon (carbon layer) as the first layer and a layer containing metal powder (metal particle-containing layer, etc.) or a metal foil as the second layer.
[0148] When the cathode lead layer includes a metal foil or a metal particle-containing layer, the entire cathode lead layer may be composed of the metal foil or the metal particle-containing layer. Alternatively, at least one of the first layer and the second layer may be composed of the metal particle-containing layer.
[0149] Examples of the conductive carbon include graphite (artificial graphite, natural graphite, etc.).
[0150] The layer containing metal powder as the second layer can be formed, for example, by laminating a composition containing metal powder on the surface of the first layer. As such a second layer, for example, a metal particle-containing layer formed using a paste containing metal powder and a resin binder can be cited. As the resin binder, a thermoplastic resin can also be used, but a thermosetting resin such as an imide resin and an epoxy resin is preferably used. From the viewpoint of easily obtaining high conductivity of the second layer, silver-containing particles can be used as the metal powder. As silver-containing particles, silver particles and silver alloy particles can be cited. The second layer can contain one type of silver-containing particles, or a combination of two or more types. The silver particles may contain a small amount of impurities.
[0151] When a metal foil is used as the first layer, the type of metal is not particularly limited. The metal foil preferably uses a valve metal (aluminum, tantalum, niobium, etc.) or an alloy containing a valve metal. The surface of the metal foil can be roughened as needed. A chemical conversion coating can be provided on the surface of the metal foil, and a coating of a metal (dissimilar metal) or a non-metallic film different from the metal constituting the metal foil can also be provided. As the dissimilar metal or non-metal, metals such as titanium or non-metals such as carbon (conductive carbon, etc.) can be listed.
[0152] The above-mentioned coating of a different metal or non-metal (for example, conductive carbon) may be used as the first layer, and the above-mentioned metal foil may be used as the second layer.
[0153] (Separator)
[0154] When a metal foil is used for the cathode lead-out layer, a separator may be arranged between the metal foil and the anode foil as the anode body. The separator is not particularly limited, and for example, a nonwoven fabric containing fibers of cellulose, polyethylene terephthalate, vinylon, or polyamide (e.g., aliphatic polyamide, aromatic polyamide such as aramid) may be used.
[0155] (other)
[0156] The electrolytic capacitor includes at least one capacitor element. The electrolytic capacitor may be a winding type, a chip type, or a stacked type. For example, the electrolytic capacitor may include a plurality of stacked capacitor elements. In addition, the electrolytic capacitor may include two or more winding capacitor elements. The structure of the capacitor element may be selected according to the type of the electrolytic capacitor.
[0157] [Method for manufacturing electrolytic capacitor]
[0158] The electrolytic capacitor is formed, for example, by a manufacturing method including a first step of preparing an anode body, a second step of forming a dielectric layer on at least a portion of the surface of the anode body, and a third step of forming a solid electrolyte layer covering at least a portion of the aforementioned dielectric layer. The manufacturing method may also include a fourth step of forming a cathode lead layer covering the solid electrolyte layer. Through the first step to the third step (or the fourth step), a capacitor element is formed. The manufacturing method of the electrolytic capacitor may also include a fifth step of connecting the lead terminal to the capacitor element, and a sixth step of sealing the capacitor element.
[0159] (1st step)
[0160] In the first step, an anode body having a porous portion at least on the surface layer and having a first end and a second end is prepared. When the anode body is an anode foil, for example, as described above, the metal foil is etched to obtain an anode foil having a porous portion on the surface layer. The etching treatment can be performed by electrolytic etching or chemical etching. When the anode body is a porous formed body or a porous sintered body, for example, particles containing a valve metal are formed, and the formed body obtained by forming is sintered to obtain the anode body.
[0161] (Second step)
[0162] In the second step, a dielectric layer is formed on at least a portion of the surface of the anode body. The dielectric layer is formed by, for example, anodic oxidation of the valve action metal on the surface of the anode body by chemical conversion treatment or the like.
[0163] (Step 3)
[0164] In the third step, for an anode body having a dielectric layer, a solid electrolyte layer is formed in a manner covering at least a portion of the dielectric layer. The solid electrolyte layer is formed on the second end side in the anode body having a dielectric layer. Moreover, as described above, the solid electrolyte layer has a first portion arranged in the voids of the porous portion and a second portion arranged on the outside of the main surface of the aforementioned anode body having a dielectric layer. The second portion includes n or more conductive polymer layers on a main surface of the anode body having a dielectric layer. n can be selected from the above range. Through the third step, at the second end, a solid electrolyte layer is formed in a manner such that the thickness Tt and the ratio Tt / n of the second portion are within the above range.
[0165] More specifically, the third step includes at least:
[0166] Sub-step A of treating the second end side of the anode body having the dielectric layer with a first treatment liquid containing a first conductive polymer or a precursor thereof;
[0167] After sub-step A, sub-step B of treating the second end side of the anode body with a second treatment liquid containing at least a cationic agent;
[0168] After sub-step B, sub-step C of treating the second end side of the anode body with a third treatment liquid containing a second conductive polymer and a water-soluble polymer; and
[0169] Repeat sub-steps B and C of sub-step D.
[0170] In sub-step D, sub-step B and sub-step C may be repeated (n-1) times.
[0171] (Sub-step A)
[0172] In sub-step A, a first treatment solution containing a conjugated polymer precursor and a dopant may be used to chemically polymerize and / or electrolytically polymerize the conjugated polymer precursor on the dielectric layer, thereby forming a layer containing a first conductive polymer (first conductive polymer layer), wherein the first conductive polymer contains a conjugated polymer and a dopant. The precursor may be at least one selected from monomers, oligomers, and prepolymers of conjugated polymers.
[0173] When a treatment liquid containing a conjugated polymer precursor is used, an oxidant is used to polymerize the precursor. The oxidant may be contained in the treatment liquid as an additive. In addition, the oxidant may be applied to the anode body before or after the treatment liquid is brought into contact with the anode body on which the dielectric layer is formed. Examples of such oxidants include those capable of generating Fe 3+Compounds (ferric sulfate, etc.), persulfates (sodium persulfate, ammonium persulfate, etc.), hydrogen peroxide. The oxidizing agent may be used alone or in combination of two or more.
[0174] Alternatively, the first conductive polymer layer may be formed by bringing a first treatment liquid (solution or dispersion) containing a first conductive polymer into contact with the dielectric layer. Usually, after bringing the first treatment liquid into contact with the dielectric layer, a drying treatment (heat drying, etc.) is performed.
[0175] The attachment and polymerization (or drying) of the first treatment liquid to the anode body having the dielectric layer may be performed once or repeated multiple times. In the case of repeated multiple times, the composition and viscosity of the first treatment liquid may be the same in each time, or at least one of the conditions may be changed.
[0176] When the first conductive polymer layer contains a water-soluble polymer, the first treatment liquid may also contain a water-soluble polymer. For the components contained in the first conductive polymer layer, the description about the solid electrolyte layer or the first part can be referred to.
[0177] If necessary, sub-step A and sub-step B can be repeated alternately before sub-step C.
[0178] (Sub-step B)
[0179] In sub-step B, after sub-step A, the second end side of the anode body is treated with a second treatment liquid. The second treatment liquid contains at least a cationic agent. The second treatment liquid may contain a cationic agent and an anionic agent. The second treatment liquid may also contain a surfactant. As the components contained in the second treatment liquid, reference can be made to the description of the continuous or discontinuous layer described above.
[0180] (Sub-step C)
[0181] In sub-step C, after sub-step B, a third treatment liquid containing a second conductive polymer (and a water-soluble polymer) is brought into contact with the portion on the second end side of the anode body. After the third treatment liquid is brought into contact with the portion on the second end side, a drying treatment (heat drying, etc.) is usually performed. In this way, a second conductive polymer layer containing a second conductive polymer (and a water-soluble polymer) is formed.
[0182] Regarding the components contained in the third treatment liquid, refer to the description regarding the solid electrolyte layer or Part 2.
[0183] The concentration of the water-soluble polymer in the third treatment liquid may be 1% to 15% by mass, or 5% to 15% by mass. When the concentration of the water-soluble polymer is within this range, it is easy to adjust the thickness Tt and the ratio Tt / n to the above range.
[0184] (Sub-step D)
[0185] In sub-step D, sub-step B and sub-step C are repeated (n-1) times. In this way, the number of layers n of the second conductive polymer layer can be adjusted, and the thickness Tt of the second portion can be adjusted.
[0186] (Step 4)
[0187] In the fourth step, a cathode lead layer is formed. The cathode lead layer is formed by a known method depending on the layer structure.
[0188] For example, when the cathode lead layer includes a metal foil as the first layer or the second layer, the metal foil is stacked in a manner covering at least a portion of the solid electrolyte layer or the first layer, thereby forming the first layer or the second layer. The first layer including conductive particles is formed, for example, by applying a conductive paste or liquid dispersion containing conductive particles and a resin binder (water-soluble resin, curable resin, etc.) as required to the surface of the solid electrolyte layer. The second layer including metal powder is formed, for example, by applying a paste containing metal powder and a resin binder to the surface of the first layer. In the formation process of the cathode lead layer, drying treatment, heat treatment, etc. may also be performed as required.
[0189] (5th step)
[0190] In the fifth step, the lead terminal is connected to the capacitor element. In the capacitor element, the cathode lead layer may be electrically connected to one end of the cathode lead terminal. The cathode lead terminal is, for example, coated with a conductive adhesive on the cathode lead layer and bonded to the cathode lead layer via the conductive adhesive. One end of the anode lead terminal may also be electrically connected to the anode lead portion of the anode body.
[0191] The other ends of the anode lead terminal and the cathode lead terminal are respectively drawn out from the resin outer package or the case when the capacitor element is sealed in step 6. The other ends of each terminal exposed from the resin outer package or the case are used for welding connection with a substrate on which the electrolytic capacitor is to be mounted.
[0192] The fifth step is not limited to the case where the lead terminal is led out. In the fifth step, for example, the lead frame may be connected to the capacitor element. In this case, in the sixth step, the end face of the lead frame may be exposed from the outer surface of the resin outer package. In addition, in the fifth step, at least one end face of the anode portion and the cathode portion may be exposed from the outer surface of the resin outer package in the sixth step. The end face of the lead frame, the end face of the anode portion, and the end face of the cathode portion exposed in the sixth step are electrically connected to the external electrode.
[0193] (Step 6)
[0194] The capacitor element is sealed with a resin outer body or a shell. For example, the material resin of the capacitor element and the outer body (for example, an uncured thermosetting resin and a filler) can be contained in a mold, and the capacitor element can be sealed with a resin outer body by transfer molding, compression molding, etc. At this time, the anode lead terminal and the cathode lead terminal connected to the anode lead drawn from the capacitor element are exposed from the mold respectively. In addition, the capacitor element can also be contained in a bottomed shell in a manner where the other end side of the anode lead terminal and the cathode lead terminal is located on the opening side of the bottomed shell, and the opening of the bottomed shell is sealed with a sealant, thereby forming an electrolytic capacitor.
[0195] Figure 1 This is a cross-sectional view schematically showing the structure of a solid electrolytic capacitor according to one embodiment of the present disclosure. Figure 1 2 is a schematic cross-sectional view of a solid electrolytic capacitor in a direction parallel to both the length direction and the thickness direction of the capacitor element 2. Figure 1 As shown, the solid electrolytic capacitor 1 includes a capacitor element 2, a resin outer package 3 that seals the capacitor element 2, and an anode lead terminal 4 and a cathode lead terminal 5, at least a portion of which is exposed to the outside of the resin outer package 3. The anode lead terminal 4 and the cathode lead terminal 5 can be made of metal such as copper or a copper alloy. The resin outer package 3 has a substantially rectangular parallelepiped shape, and the solid electrolytic capacitor 1 also has a substantially rectangular parallelepiped shape.
[0196] The capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode portion 8 covering the dielectric layer 7. The cathode portion 8 includes a solid electrolyte layer 9 covering the dielectric layer 7 and a cathode lead layer 10 covering the solid electrolyte layer 9. The cathode lead layer 10 includes a carbon layer 11 covering the solid electrolyte layer 9 and a metal particle-containing layer 12 covering the carbon layer 11.
[0197] The anode body 6 includes a region facing the cathode portion 8 and a region not facing the cathode portion 8. In the region of the anode body 6 not facing the cathode portion 8, an insulating separation portion (insulating region) 13 is formed in a band-shaped manner to cover the surface of the anode body 6 and is adjacent to the cathode portion 8, thereby limiting the contact between the cathode portion 8 and the anode body 6. The other portion of the region of the anode body 6 not facing the cathode portion 8 is electrically connected to the anode lead terminal 4 by welding. The cathode lead terminal 5 is electrically connected to the cathode portion 8 via an adhesive layer 14 formed using a conductive adhesive.
[0198] [Example]
[0199] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0200] Follow the steps below to make Figure 1The electrolytic capacitor 1 shown was used to evaluate its characteristics.
[0201] (1) Step of Preparing Anode Body 6 (First Step)
[0202] Anode body 6 was produced by roughening both surfaces of an aluminum foil (thickness: 100 μm) as a base material by etching.
[0203] (2) Step of forming dielectric layer 7 (second step)
[0204] The second end portion of anode body 6 was immersed in a chemical conversion solution, and a DC voltage of 70 V was applied for 20 minutes to form dielectric layer 7 containing aluminum oxide.
[0205] (3) Step of forming solid electrolyte layer 9 (third step)
[0206] (3-1) Sub-step A
[0207] Under stirring, 3,4-ethylenedioxythiophene monomer was added to an aqueous solution of polystyrene sulfonic acid (Mw: 75000), and then an oxidant (iron (III) sulfate and sodium persulfate) was added to perform chemical oxidative polymerization. The obtained polymerization solution was filtered using an ion exchange device to remove impurities, thereby obtaining a solution containing poly(3,4-ethylenedioxythiophene) (PEDOT) as a conjugated polymer and polystyrene sulfonic acid (PSS) as a dopant.
[0208] Pure water was added to the obtained solution, and the mixture was homogenized with a high pressure homogenizer, and further filtered with a filter to prepare a first treatment liquid in the form of a dispersion. The concentration of the first conductive polymer (PEDOT and PSS) in the first treatment liquid was 2% by mass.
[0209] After the portion on the second end side of the anode body 6 having the dielectric layer 7 obtained in the second step (2) is immersed in the first treatment liquid, it is taken out from the first treatment liquid and further dried at 120° C. for 10 to 30 minutes. By further repeating the immersion in the first treatment liquid and the drying once each, at least a portion of the first portion including the first conductive polymer is formed in a manner that covers the surface of the dielectric layer 7 and fills at least a portion of the concave portion of the porous portion.
[0210] (3-2) Sub-step B
[0211] N,N-dimethyloctylamine (cationic agent) and a copolymer of styrenesulfonic acid and phosphoryloxyethyl acrylate (P(=O)(OH)2-O-CH2CH2-OC(=O)-CH=CH2) (anionic agent) were dissolved in pure water to prepare a second treatment liquid. The concentration of the cationic agent in the second treatment liquid was set to 0.05 mol / L, and the concentration of the anionic agent was set to 0.03 mol / L.
[0212] The second end portion of anode body 6 treated in sub-step A is immersed in the second treatment liquid, taken out, and further dried at 100° C. for 3 minutes, thereby allowing the cationic agent and the anionic agent to adhere to the surface of the first conductive polymer.
[0213] In addition, the said anion agent used for the 2nd process liquid was manufactured as follows.
[0214] Sodium styrene sulfonate and acrylate phosphoryloxyethyl are added to a specified amount of pure water and mixed to prepare a monomer solution. At this time, sodium styrene sulfonate and acrylate phosphoryloxyethyl are used in a ratio of 75:25 in which the copolymerization ratio (molar ratio) of styrene sulfonic acid and acrylate phosphoryloxyethyl in the copolymer is 75:25. Under stirring, a specified amount of ammonium persulfate (oxidant) is added to the monomer solution, and a polymerization reaction is carried out for 8 hours. Pure water and ion exchange resin are added to the obtained polymer solution and stirred and filtered, thereby performing a purification process. The purification process is repeated many times to finally obtain the above-mentioned copolymer. The molecular weight of the copolymer is measured by GPC, and the weight average molecular weight (Mw) is 83000.
[0215] (3-3) Sub-step C
[0216] A solution containing PEDOT and PSS was obtained in the same manner as in the above sub-step A (3-1). Pure water and an acrylic acid-methacrylic acid copolymer (water-soluble polymer) having a weight average molecular weight (Mw) as shown in Table 1 as required were added to the obtained solution, homogenized with a high-pressure homogenizer, and then filtered with a filter to prepare a third treatment liquid in the form of a dispersion. The concentration of the second conductive polymer in the third treatment liquid was 4% by mass, and the concentration of the water-soluble polymer was 11% by mass.
[0217] The second end portion of anode body 6 obtained in sub-step B is immersed in the third treatment solution, taken out, and further dried at 120° C. for 10 to 30 minutes. Thus, one second conductive polymer layer is formed.
[0218] (3-4) Sub-step D
[0219] The portion on the second end side of the anode body 6 obtained in sub-step C is provided to sub-step B using the above-mentioned second treatment liquid. The portion on the second end side of the anode body 6 obtained in this sub-step B is provided to sub-step C using the above-mentioned third treatment liquid. Sub-step B and sub-step C are further repeated alternately as needed. In sub-step D, by repeating sub-step B and sub-step C a total of (n-1) times each, a solid electrolyte layer 9 having n layers of the second conductive polymer layer shown in Table 1 is formed. Most of the second conductive polymer layer constitutes the second portion formed on the main surface of the anode body 6, and a portion of the second conductive polymer layer is sometimes filled in the recessed portion of the porous portion of the anode body 6.
[0220] In the example where the second portion contains a water-soluble polymer, the content of the water-soluble polymer in the second portion determined by the above-described procedure is 10% by mass to 20% by mass.
[0221] (4) Step of forming cathode lead layer 10
[0222] The portion on the second end side of the anode body 6 obtained in the third step (3) is immersed in a dispersion in which graphite particles are dispersed in water, taken out from the dispersion, and then dried, thereby forming a first layer (carbon layer) 11 at least on the surface of the solid electrolyte layer 9. The drying is performed at 130 to 180° C. for 10 to 30 minutes.
[0223] Next, a silver paste containing silver particles and a binder resin (epoxy resin) is applied to the surface of the first layer 11, and heated at 150 to 200° C. for 10 to 60 minutes to cure the binder resin, thereby forming the second layer (metal particle-containing layer) 12. In this way, the cathode extraction layer 10 composed of the first layer 11 and the second layer 12 is formed.
[0224] As described above, capacitor element 2 is produced.
[0225] (5) Assembly of electrolytic capacitors
[0226] The cathode lead layer 10 of the capacitor element 2 obtained in the above step (4) is bonded to one end of the cathode lead terminal 5 via an adhesive layer made of a conductive adhesive. The first end of the anode body 6 protruding from the capacitor element 2 is bonded to one end of the anode lead terminal 4 by laser welding.
[0227] Next, resin outer package 3 made of insulating resin is formed around capacitor element 2 by transfer molding. At this time, the other end of anode lead terminal 4 and the other end of cathode lead terminal 5 are drawn out of resin outer package 3 .
[0228] Thus, the electrolytic capacitor 1 was completed. Similarly to the above, a total of 20 electrolytic capacitors 1 were produced for each example.
[0229] (6) Evaluation
[0230] The following evaluation was performed using an electrolytic capacitor.
[0231] (a) Thickness Tt and ratio Tt / n
[0232] Through the above steps, the thickness Tt (μm) of the second portion and the number n of the second conductive polymer layer are determined, and the ratio Tt / n (μm) is calculated from these.
[0233] (b) Initial electrostatic capacitance (Cap) and ESR
[0234] In an environment of 20°C, a 4-terminal LCR meter was used to measure the initial electrostatic capacitance (μF) of each electrolytic capacitor at a frequency of 120Hz, and the initial ESR (mΩ) at a frequency of 100kHz was measured. Then, the average value of the initial electrostatic capacitance (Cap) and ESR of 20 electrolytic capacitors was calculated.
[0235] (c) Leakage current (LC)
[0236] A resistor of 1 kΩ was connected in series to the electrolytic capacitor, and a leakage current (μA) was measured after a rated voltage of 10 V was applied by a DC power supply for 20 seconds. The average value of 20 electrolytic capacitors was obtained.
[0237] (d) Voltage resistance
[0238] For 10 electrolytic capacitors among the electrolytic capacitors for which LC was measured, a voltage was applied while increasing the voltage at a rate of 1.0 V / sec, and a breakdown withstand voltage (V) was measured when an overcurrent of 0.5 A flowed. Then, an average value of the 10 electrolytic capacitors was calculated.
[0239] The evaluation results are shown in Table 1. In Table 1, A1 to A3 are Examples, and B1 to B5 are Comparative Examples.
[0240] [Table 1]
[0241]
[0242] As shown in Table 1, in the embodiment, compared with the comparative example, it is possible to suppress the leakage current to a low level while ensuring a higher electrostatic capacitance and a lower ESR, and to ensure a higher withstand voltage. This is because the thickness Tt and the ratio Tt / n of the second part satisfy 18.0μm≤Tt≤50.0μm and 9.0μm≤Tt / n≤12.5μm, respectively. When Tt<18.0μm, the withstand voltage is significantly reduced (comparison of B2 and B4 with A3). Even in the case of Tt<18.0μm, when the number of the second conductive polymer layer n is 1, the leakage current is also small (B4). It is believed that this is because the stress caused by heat shrinkage is suppressed to a low level due to the small number of heating and drying, and the occurrence of defects in the dielectric layer is suppressed. However, in the case of Tt<18.0μm and n=2, the leakage current becomes significantly larger (comparison of B4 with B2). It is believed that this is because, in addition to the small Tt, a greater stress is applied to the dielectric layer due to heat shrinkage, which easily causes defects. In addition, when Tt>50μm, high withstand voltage is obtained, but leakage current increases (comparison of B1 and B5 with A2). This is believed to be because n needs to be increased in order to increase thickness Tt, and the number of heating and drying increases, which increases stress caused by thermal shrinkage and easily generates defects in the dielectric layer.
[0243] Even when 18.0μm≤Tt≤50.0μm is satisfied, when Tt / n<9.0μm, the withstand voltage is low and the ESR increases compared to the case of Tt / n≥9.0μm (comparison of B3 with A1 and A2). In the case of 18.0μm≤Tt≤50.0μm and Tt / n<9.0μm, even if a certain degree of conductivity can be ensured by the second conductive polymer layer, n also increases. Therefore, the interface resistance between adjacent second conductive polymer layers increases. Therefore, it is believed that the conductivity of the second part as a whole becomes lower and the ESR increases. In addition, according to the comparison of B3 with A1 and A2, when the second conductive polymer layer contains a water-soluble polymer, it is easy to form a conductive polymer layer with a relatively uniform thickness, and there is a tendency for the withstand voltage to be further improved.
[0244] It should be noted that when the weight average molecular weight (Mw) of the water-soluble polymer is more than 50,000 and less than 800,000, it is easy to adjust the ratio Tn / n to the range of 9.0 μm ≤ Tt / n ≤ 12.5 μm compared to the case where the weight average molecular weight (Mw) is outside the range. Therefore, even if n is less, it is easy to adjust the thickness Tt to meet 18.0 μm ≤ Tt ≤ 50.0 μm. Thus, it is easy to reduce the stress applied to the dielectric layer due to the thermal contraction of the second conductive polymer layer, and the total of the interface resistance between the adjacent second conductive polymer layers can be reduced. Therefore, it is easy to further reduce the leakage current and obtain higher withstand voltage. Moreover, since it is easy to ensure the high conductivity of the second part as a whole, it is easy to obtain low ESR. In addition, when the weight average molecular weight (Mw) of the water-soluble polymer is more than 50,000 and less than 800,000, it is easy to form a second conductive polymer layer with a relatively uniform film quality and thickness.
[0245] Industrial Applicability
[0246] The present disclosure can provide a high-quality electrolytic capacitor, thereby enabling the electrolytic capacitor to be used in various applications.
Claims
1. An electrolytic capacitor comprising at least one capacitor element, the capacitor element comprising: an anode body including a porous portion in a surface layer; a dielectric layer covering at least a portion of the surface of the anode body; and a solid electrolyte layer covering at least a portion of the dielectric layer, The anode body has a first end and a second end opposite to the first end. The solid electrolyte layer is formed on a portion of the anode body having the dielectric layer including the second end portion, and has a first portion arranged in the voids of the porous portion and a second portion arranged outside the main surface of the anode body having the dielectric layer, The second portion includes n or more conductive polymer layers on the main surface of the anode body having the dielectric layer, and satisfies the following relationship: 18.0μm≤Tt≤50.0μm 9.0μm≤Tt / n≤12.5μm in, n is an integer greater than or equal to 2, and Tt is a thickness of the second portion on one main surface of the anode body having the dielectric layer at the second end portion.
2. The electrolytic capacitor according to claim 1, wherein: n is 4 or less.
3. The electrolytic capacitor according to claim 1 or 2, wherein: Satisfies 20.0μm<Tt.
4. The electrolytic capacitor according to claim 1 or 2, wherein: The second part comprises a water-soluble polymer, The water-soluble polymer has a weight average molecular weight of 50,000 or more and 800,000 or less.
5. The electrolytic capacitor according to claim 4, wherein: The content of the water-soluble polymer in the second portion is 10% by mass or more and 20% by mass or less.
6. The electrolytic capacitor according to claim 1 or 2, wherein: The second portion includes at least one continuous or discontinuous layer interposed between adjacent conductive polymer layers among the n or more conductive polymer layers. The continuous or discontinuous layer comprises at least a cationic agent.
7. A method for manufacturing an electrolytic capacitor, comprising: In a first step, an anode body is prepared, which includes a porous portion in a surface layer and has a first end and a second end opposite to the first end; A second step of forming a dielectric layer on at least a portion of the surface of the anode body; and The third step is to form a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer is formed on a portion of the anode body having the dielectric layer including the second end portion, and has a first portion arranged in the voids of the porous portion and a second portion arranged outside the main surface of the anode body having the dielectric layer, The second portion includes n or more conductive polymer layers on the main surface of the anode body having the dielectric layer. The third step comprises: Sub-step A of treating the portion of the anode body having the dielectric layer including the second end portion with a first treatment solution containing a first conductive polymer or a precursor thereof; After the sub-step A, a sub-step B of treating the portion of the anode body including the second end with a second treatment solution containing at least a cationic agent; After the sub-step B, a sub-step C of treating the portion of the anode body including the second end with a third treatment solution including a second conductive polymer and a water-soluble polymer; and Repeat sub-step B and sub-step D of sub-step C, In the third step, the solid electrolyte layer is formed so as to satisfy the following relationship: 18.0μm≤Tt≤45.0μm 9.0μm≤Tt / n≤12.5μm Here, n is an integer greater than or equal to 2, and Tt is a thickness of the second portion on the main surface of the anode body having the dielectric layer at the second end portion.
8. The method for manufacturing an electrolytic capacitor according to claim 7, wherein: In the sub-step D, the sub-step B and the sub-step C are repeated (n-1) times.
9. The method for manufacturing an electrolytic capacitor according to claim 7 or 8, wherein: The n is 2 or more and 4 or less.
10. The method for manufacturing an electrolytic capacitor according to claim 7 or 8, wherein: The water-soluble polymer has a weight average molecular weight of 50,000 or more and 800,000 or less.
11. The method for manufacturing an electrolytic capacitor according to claim 7 or 8, wherein: The concentration of the water-soluble polymer in the third treatment liquid is 1 mass % or more and 15 mass % or less.
Citation Information
Patent Citations
Method for manufacturing solid electrolytic capacitor
WO2014087617A1
Electrolytic capacitor and method for producing same
WO2021132223A1